Can`t pay, can`t play? Talent lead`s perspectives on the financial constraints experienced by athletes on the England Talent Pathway* - Morley, D.; McKenna, J.; Gilbert, S.; French, J.; Till, K.; Quarmby, T.; Turner, G. (High Ability Studies, 2018)
This study explored the extent of financial constraints experienced by athletes on the England Talent Pathway, as perceived by talent leads from various sports. Using a mixed-methods approach, 34 participants completed online surveys with 26 follow-up interviews. Findings showed the prevalence of financial constraints on individuals within the system, with three emerging themes: costs; demands on athletes; and potential funding support. "Pinch points", causing the greatest severity of financial constraint, emerged further along the pathway and there were infrequent examples of mechanisms to identify talented athletes experiencing financial hardship. A means-tested system, premised on the demonstration of potential, is suggested by talent leads as a way of providing funding for athletes to ameliorate financial constraints in the future.